PENGGUNAAN MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI PADA SISWA SMA MUHAMMADIYAH 1 METRO TAHUN PELAJARAN 2010/2011 - Ratini, Ratini (UNIVERSITAS MUHAMMADIYAH METRO, 2011)
The objective of the research are to increase the student activities and learning achievement of Biology. The research conducted in class Â SMA Muhammadiyah 1 Metro Academic Year 2010/2011 by using Classroom Action Research. There are two cycle in the research with tree meeting every cycle. The result of the research show that interactive multimedia can increase the student activities and learning achievement of Biology. Score average before usingÂ Classroom Action Research is 28,23% and increase to 59,77% in cycle II. The reseacher suggest that interactive multimedia can implement to increase the student activities and learning achievement of Biology. Implementing of interactive multimedia make the students interesting to the learning.Â Kata kunci: Multimedia Interaktif, Aktivitas Belajar, Hasil Belajar